2013
DOI: 10.1158/0008-5472.can-13-1462
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Glucuronidation: An Unexpected Target for Androgen Deprivation Therapy, with Prognosis and Diagnostic Implications

Abstract: Androgen deprivation therapy (ADTh) remains a mainstay of prostate cancer treatment, but its efficacy is bypassed by mechanisms that are not fully understood. In human prostate cancer cells, androgen glucuronidation, catalyzed by the two UDP-glucuronosyltransferase (UGT) enzymes UGT2B15 and UGT2B17, is the major androgen inactivation pathway. In this study, we investigated the effect of ADTh on androgen glucuronidation to evaluate its potential clinical utility for prostate cancer prognosis or therapy. UGT2B15… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 42 publications
4
40
0
Order By: Relevance
“…Similar regulation of other UGT enzymes after DNA-PKcs depletion (Fig 3B) argues against functional redundancy impacting DHT levels. The overall findings are of translational significance, as UGT2B15 and 2B17 are being developed as prognostic markers and therapeutic targets in PCa (Grosse et al, 2013), and the mechanisms of regulation are not well understood. To assess clinical relevance, a cohort of 232 patients with high-risk localized PCa was examined, wherein it was observed that both UGT2B15 (correlation coefficient −0.28, p<0.0001) and UGT2B17 (correlation coefficient −0.38, p<0.0001) expression strongly negatively correlated with DNA-PKcs (Fig 3H), supporting the concept that DNA-PKcs suppresses expression of UGT enzymes in human tumors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar regulation of other UGT enzymes after DNA-PKcs depletion (Fig 3B) argues against functional redundancy impacting DHT levels. The overall findings are of translational significance, as UGT2B15 and 2B17 are being developed as prognostic markers and therapeutic targets in PCa (Grosse et al, 2013), and the mechanisms of regulation are not well understood. To assess clinical relevance, a cohort of 232 patients with high-risk localized PCa was examined, wherein it was observed that both UGT2B15 (correlation coefficient −0.28, p<0.0001) and UGT2B17 (correlation coefficient −0.38, p<0.0001) expression strongly negatively correlated with DNA-PKcs (Fig 3H), supporting the concept that DNA-PKcs suppresses expression of UGT enzymes in human tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Factors influencing UGT expression in non-prostatic tissues include NRF and Sp1 (Mackenzie et al, 2010), and influence on these factors may contribute to the impact of DNA-PKcs. Since UGT2B15 and 2B17 are being evaluated as pharmacologic targets for PCa management (Grosse et al, 2013), the identified link to DNA-PKcs may prove important in designing therapeutic regimens.…”
Section: Discussionmentioning
confidence: 99%
“…They stimulate androgen removal and are implicated in PCa (27). UGT2B15 and UGT2B17 are directly repressed by AR in an agonist-dependent manner (28).…”
Section: Resultsmentioning
confidence: 99%
“…Because of these and related findings, yet other means to target AR for CaP treatment are being explored. Such efforts are directed for instance at identifying and exploiting the differences in the AR protein interactome that is associated with wild-type or mutant AR, development of novel agents that interfere with the ligand-independent activity of AR 52,53, modulation of the degradation rather than synthesis of intratumoral androgens 54, or combined administration of an AR antagonist and an GR antagonist 49. In the era of precision medicine, it has been proposed to tailor administration of these treatments based on a CaP's expression status of (mutant) AR, pattern of expression or structural integrity of steroidogenic enzymes.…”
Section: Alternative Approaches To Inhibits Ar's Action On Cap Cells mentioning
confidence: 99%